2016
DOI: 10.21037/jtd.2016.03.72
|View full text |Cite
|
Sign up to set email alerts
|

Importance of fractional exhaled nitric oxide in diagnosis of bronchiectasis accompanied with bronchial asthma

Abstract: Clinical FeNO measurement is a simple, noninvasive, and rapid method used to differentiate asthmatic from nonasthmatic patients with BE. This technique exhibits potential for asthma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…Since then, some studies have reported a direct link between bronchiectasis and bronchial hyperreactivity or atopy. [ 29 , 30 ] In our study, however, we did not identify a positive relationship between bronchiectasis and atopy. In addition, the higher level of serum eosinophils we observed in patients with coexistent bronchiectasis suggests that the presence of bronchiectasis could potentially be used to identify a phenotype of patients with severe eosinophilic asthma (SEA).…”
Section: Discussioncontrasting
confidence: 88%
“…Since then, some studies have reported a direct link between bronchiectasis and bronchial hyperreactivity or atopy. [ 29 , 30 ] In our study, however, we did not identify a positive relationship between bronchiectasis and atopy. In addition, the higher level of serum eosinophils we observed in patients with coexistent bronchiectasis suggests that the presence of bronchiectasis could potentially be used to identify a phenotype of patients with severe eosinophilic asthma (SEA).…”
Section: Discussioncontrasting
confidence: 88%
“…In fact, few studies have assessed FeNo in subjects with asthma and bronchiectasis. In a recent retrospective study, Chen et al [ 61 ] measured FeNO levels in 99 patients with bronchiectasis (20 of them with asthma) and found higher FeNO levels in subjects with bronchiectasis and asthma, compared to subjects who had only bronchiectasis. The authors also demonstrated that FeNO levels can help distinguish patients with bronchiectasis and asthma from those with bronchiectasis but not asthma, and they established a cut-off point of 22.5 ppb, with an estimated AUC-ROC of 0.832.…”
Section: Discussionmentioning
confidence: 99%
“…symptoms alone, acute reversibility of airway obstruction, bronchial hyperresponsiveness, asthma biomarkers like exhaled nitric oxide (NO) or blood/sputum eosinophils). For instance, CHEN et al [119] suggested that exhaled NO could be a good biomarker to identify asthma in bronchiectasis patients but further investigation is needed to validate its use. In a large database of >150 patients, almost 20% of them had a sputum eosinophil percentage ⩾3%, suggesting some degree of airway eosinophilic inflammation [23].…”
Section: Asthma In Patients With Bronchiectasismentioning
confidence: 99%